THE ASSOCIATION BETWEEN STOCK PRICES AND MACROECONOMIC VARIABLES. IS THERE A LINK BETWEEN THE JCI, INTEREST RATES, INFLATION AND THE EXCHANGE RATE IN INDONESIA? - Zubaidah, Dyah Dwi; Kaluge, David; Ekawaty, Marlina (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
The long-term relationship between JCI (Jakarta Composite Index), exchange rates, interest rates, and inflation in Indonesia is crucial for economic stability, policymaking, market performance, and investment decisions. The data from Januari 208-December 2022 show some findings. The analysis by VECM indicates a positive feedback loop between the stock market index and bank reserves, with inflation positively impacting the stock market index. The exchange rate is influenced by all three variables. Over time, the influence of the BI rate on the stock market increases, inflation fluctuates, and the exchange rate's influence decreases. The ability of JCI and inflation to affect the exchange rate grows, while the exchange rate stabilizes but gradually declines after an initial rise. Policymakers can use the insights from the positive feedback loop between the stock market index and bank reserves to design policies that promote a stable and mutually reinforcing relationship between these variables. It is due to any fluctuations in the stock market index, bank reserves, or inflation could potentially impact the exchange rate, affecting the competitiveness of Indonesian goods and services in the global market. For the market participants, adequate risk management strategies can be adopted to mitigate potential risks arising from these variables.